Lars Saabye Christensen, "Bunica mea chinezoaică" (Min kinesiske farmor/My Chinese Grandmother), traducere din limbile norve-giană și daneză cu note de Sanda Tomescu Baciu, Cluj-Napoca: Casa Cărții de Știință, 2022, 232 p. - DREVE, Roxana-Ema (Studia Universitatis Babeș-Bolyai Philologia, 2023)
The aged photo of a ship would normally not determine you to return to the first pages of a text and read it again and again. But if you are the reader of Lars Saabye Christensen’s new book, Min kinesiske farmor [My Chinese grandmother], it does. Because Lars Saabye Christensen’s text is not only a book about the journey to China that the narrator’s grandmother took in 1906, but it is in fact a journey in itself. It takes the reader from the present to the near and far past, from Norway to Denmark and China, as it renders the power of memory and love and the changes that come along with the passing of time. Bunica mea chinezoaică [My Chinese Grandmother] is admirably translated from Norwegian and Danish by Professor Sanda Tomescu Baciu, with the financial support of NORLA (Norwegian Literature Abroad) and appeared in 2022 at Casa Cărții de Știință publishing house. It brings a flood of memories revolving around S/S Protector, whose picture we can see on the cover of the Romanian translation of the novel, thanks to Professor Sanda Tomescu Baciu and M/S Maritime Museum of Denmark.